Applications of contemporary artificial intelligence technology in forensic odontology as primary forensic identifier : A scoping review - Norhasmira, Mohammad; Rohana, Ahmad; Arofi, Kurniawan; Mohd Yusmiaidil, Putera Mohd Yusof (Frontiers Media SA, 2022)
Background: Forensic odontology may require a visual or clinical method during identification. Sometimes it may require forensic experts to refer to the existing technique to identify individuals, for example, by using the atlas to estimate the dental age. However, the existing technology can be a complicated procedure for a large-scale incident requiring a more significant number of forensic identifications, particularly during mass disasters. This has driven many experts to perform automation in their current practice to improve efficiency.